How are the Great Plains Shelterbelts - Munns, E. N.; Stoeckeler, Joseph H. (Indian Forester, 1947)
Data presented here give details of survival and growth of the shelterbelts planted from 1936-1943 by the U.S. Forest Service in its Prairie States Forestry Project and by tho Soil Conservation Service. The information is based on a systematic survey of 1,072belts. The outstanding features brought out are tho widespread interest of farmers and ranchers in the program, the better than-expected survival and growth, a wide variety of benefits and values already derived from the comparatiyely young belts, the great importance of adequate cultivation, and some interesting silvical and management problems that are beginning to show up.